Youtube as A Learning Platform in EFL Speaking Class and Anxiety Reduction - Ramli Ramli; Vivit Rosmayanti; Winarno Winarno; Fitriawati Fitriawati (Universitas Muhammadiyah Enrekang, 2024)
This study investigated the effect of YouTube on increasing students' speaking skills and determining whether using YouTube in an English classroom affects students' anxiety. This study was conducted quantitatively. The population involved 2 classes, experimental and control, in the English Education department at Universitas Borneo Tarakan, containing 70 students. The experimental class was treated with YouTube, and the control class was taught traditionally. Data were collected through a spoken test for all samples and a questionnaire to observe the students’ anxiety after using Youtube. Then, a t-test was selected to analyze the test data and a Likert scale for the questionnaire. The study discovered that the average increase in the experimental group's speaking ability score was 2.86 ± 0.54, higher than in the control group's speaking ability score of 1.03 ± 0.74. The anxiety of the 36 respondents in the experimental group, at most 33 respondents (91.7%)—had a medium level of anxiety, and the other three respondents (8.3%) had a low level of anxiety. It implied that technology such as Youtube contributed to improving students’ speaking, assisting teachers to create learning activities, and reducing anxiety.